A study on the use of text messaging among Diploma in Office Management and Technology students in UiTM Melaka / Afrah Hayati Abdul Rahman - Abdul Rahman, Afrah Hayati (2009)
The purpose of the study is to determine the influences of text messaging among Office Management and Technology (DOMT) students. This includes describing the purposes of text messaging among Diploma in Office Management and Technology (DOMT) students, the factors that attract them to text messaging and also the influences of using text messaging on DOMT students' writing ability. Data collected were analysed using the descriptive statistical analysis technique. Analyses of the questionnaires utilized the frequency percentages and included the researcher's description of the written responses from the students. This is a descriptive study with a questionnaire consists of eleven questions. Question number one to six focused on the perspectives of DOMT students on the use of text messaging. Meanwhile, question seven to ten contained the information on the factors that influenced the use of text messaging among DOMT students. Question 11 provided the answer on how text messaging had influenced DOMT students' writing ability. The results showed the various purposes of text messaging among DOMT students. In addition, there were also several factors that attracted them to text messages. The study has found that influences of using text messaging on DOMT students also gave an impact on the students' writing ability. Further findings suggest that on the whole, the use of SMS or text messaging among DOMT students was received and viewed positively by them.